Zawodówka (nie) jest OK? Szkoły zawodowe (branżowe) w opiniach uczniów a wybory edukacyjno-zawodowe w odniesieniu do sytuacji na rynku pracy - Kozielska, Joanna (Wydawnictwo Naukowe UAM, 2018)
The proposed text is an illustration of selected conclusions from a four-module research project conducted in one of the Wielkopolska counties. The aim of the empirical verification was to: make the educational and professional characteristics of the junior high school plans, get acquainted with the opinions of the employers on the situation in the local labor market, get acquainted with the plans connected with the employment of employees, get acquainted with the preparation of graduates of particular types of schools to meet the opinion of the directors of post-gymnasium schools on the state of the vocational education and to get acquainted with the opinions of the students of the upper secondary school classes on the situation on the labor market, the offer of vocational education and the self-assessment of preparation to enter the labor market. The research was conducted in the first quarter of 2016 and 2017, by the diagnostic survey method. The article is based on one of the study modules – a study of middle school students that was conducted in 2016 – the findings from the 2017 study will be cited in some places for comparative purposes only. Due to the specificity of the research topic, the selection of the research sample was random. High school students (N = 486 in 2016 and N = 490 in 2017), upper secondary school students (N = 503 – 2016 and N = 498 – 2017), upper secondary school graduates (N = 6 in 2016 and 2017 ) and the largest employers (N = 78 in 2016, N = 102 in 2017). In this project the diagnostic survey method was used as the basis. The method used to analyze the contents was made using the local traditional (printed) and internet press and the thematic work edited by the County Labor Office in Gniezno and other institutions. The main topic of this paper was the educational and vocational elections of junior high school students in the context of the situation on the local labor market (which, as it turns out, does not correspond to its needs), revealing weaknesses in vocational counseling. Regarding the specific nature of the region, attention has also been paid to the face (as opposed to the offer) of vocational education (depicted in the vocational school 2017/2018) depreciated in the eyes of the local community, which in the reality of the local labor market seems to be a rational educational choice without causing closure Road to higher education. The dissertation on vocational education has been made an additional element of publication.
Keywords: młodzież; szkoła branżowa; technikum; kształcenie zawodowe